2013
DOI: 10.4172/1948-5956.s18-003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Doxorubicin-Induced MCA-Fibrosarcoma Cytotoxicity by an Eriobotrya japonica Hydrophilic Butanol-Treated Extract through Natural Killer Cells Activation

Abstract: The combination of cytotoxic drugs with immunotherapy should be more effective than monotherapy alone since both therapeutic modalities may target different mechanisms. In addition, combination therapy may reduce adverse events associated with cytotoxic drugs. Eriobotrya japonica hydrophilic butanol-treated extract (EJWR) was found to modulate cytokines by enhancing IL-12, IFN-γ and TNF-α in vitro and in vivo and within tumor microenvironment. This was associated with enhancing survival time of mice bearing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Extraction of HE by n-butanol to yield EJ water residue (WP) was previously performed to concentrate polysaccharides, high molecular weight oligomeric procyanidins and related polyphenols and to exclude low molecular weight compounds [12,16]. This WP extract was proven to induce the release of IFN-γ from mouse spleen cells and NK cells [16,29]. In the current investigation, however, further fractionation of WP was performed using methanol:acetone to yield the MAU fraction and MAL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of HE by n-butanol to yield EJ water residue (WP) was previously performed to concentrate polysaccharides, high molecular weight oligomeric procyanidins and related polyphenols and to exclude low molecular weight compounds [12,16]. This WP extract was proven to induce the release of IFN-γ from mouse spleen cells and NK cells [16,29]. In the current investigation, however, further fractionation of WP was performed using methanol:acetone to yield the MAU fraction and MAL.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory action is mediated mainly by the triterpene acids and epicatechin isolated from Eriobotrya leaves [6,7,9,14,31]. However, studies by us and another group showed that EJ leaves polarize T helper 1 cytokines over T helper 2 cytokines [15,16,17,18,29]. Therefore, to identify the compounds or group of compounds that are responsible for the induction of IFN-γ, further sub-fractionation of MAU fraction was conducted by column chromatography using eluents with different polarities.…”
Section: Discussionmentioning
confidence: 99%
“…Four hours later 50 μL sodium dodecyl sulfate was added. When spleen was cocultured with the adherent MCA fibrosarcoma, and before adding the MTT reagent, the supernatant content of each well was carefully removed leaving the adherent MCA-fibrosarcoma in the wells 19. Absorbance was read at 570 nm by GloMax®-Multi Detection System (Promega, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Production of IL-12 is a major inducer of T helper 1(Th1) and natural killer (NK) lymphocytes and their cytokines. These produced cytokines polarize macrophages, enhance dendritic cell maturation, and lower regulatory T-cell function by inhibiting regulatory cytokines such as transforming growth factor (TGF)-β and IL-10 1619. Since it has been shown that DCA inhibits PDK and facilitates signaling pathways that lead to the inhibition of transcription factor nuclear factor of activated T-cells,2 we were encouraged to study DCA immunomodulatory activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation